A Comparative Study of the Concept of Religion According to Muslim Theologians and the Noble Verse: “Inna Al-Dīna ʿInda Allāhi Al-Islām” (Indeed, with Allāh Religion is Islam) - Sayyid Murteza Hosseini Kashani; Ali Allahbedashti; Abbas Izadpanah (آموزه‌های قرآنی, 2025)
Translation: The examination of the authority of Abrahamic religions after the advent of Islam has always been a lively and dynamic issue among theological discussions. Given the importance of uncovering the Qurʾānic perspective on this matter, transmitted evidence forms the main axis of the debates between the two sides. Among the related topics is determining the semantic application of the word “Islam” in the Qurʾān. One of the most debated verses is the noble verse “Inna ad-dīna 'inda Allāhi al-islām,” (Arabic: إِنَّ الدِّینَ عِنْدَ اللَّهِ الْإِسْلَامُ, K 3:19 Indeed, the religion in the sight of Allāh is Islam) which establishes Islam as the religion before God. Although both proponents and opponents of religious authenticity refer to this verse, an independent study that gathers and evaluates all the evidence has not yet been conducted. In this research, which emphasizes a library-analytical method, the study not only distinguishes between the two main interpretations of this verse but also evaluates the evidence for each. It then presents a third interpretation based on a different understanding of “religion” and “Islam.” This perspective defines Islam as the concept of surrender and religion as the expression of believers’ religiousness. Consequently, this research concludes that the verse is unrelated to the issue of the “authenticity of religions.” Therefore, both supporters and opponents of religious authenticity cannot regard this verse as an independent document to support their claims.